1999
DOI: 10.1002/(sici)1096-9861(19991129)414:4<437::aid-cne2>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pathology of hilar neurons in Ammon's horn sclerosis

Abstract: In addition to functionally affected neuronal signaling pathways, altered axonal, dendritic, and synaptic morphology may contribute to hippocampal hyperexcitability in chronic mesial temporal lobe epilepsies (MTLE). The sclerotic hippocampus in Ammon's horn sclerosis (AHS)‐associated MTLE, which shows segmental neuronal cell loss, axonal reorganization, and astrogliosis, would appear particularly susceptible to such changes. To characterize the cellular hippocampal pathology in MTLE, we have analyzed hilar neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 55 publications
9
65
0
3
Order By: Relevance
“…Similar findings of spine loss and dendritic swelling have also been documented in pyramidal neurons of neocortex, including sites distant from the primary epileptogenic focus [57]. Other less common dendritic abnormalities that have been described in both neocortical and hippocampal epilepsy include changes in dendritic length, shape, and branching patterns, as well as a focal increase in dendritic spines [55][56][57][58][59].…”
Section: Dendritic Abnormalities In Epilepsysupporting
confidence: 63%
See 1 more Smart Citation
“…Similar findings of spine loss and dendritic swelling have also been documented in pyramidal neurons of neocortex, including sites distant from the primary epileptogenic focus [57]. Other less common dendritic abnormalities that have been described in both neocortical and hippocampal epilepsy include changes in dendritic length, shape, and branching patterns, as well as a focal increase in dendritic spines [55][56][57][58][59].…”
Section: Dendritic Abnormalities In Epilepsysupporting
confidence: 63%
“…Such pathological specimens obtained from or near the region of the epileptic focus in neocortex or hippocampus have revealed a number of abnormalities in dendrites, but most commonly demonstrate a loss of dendritic spines [50,51]. Dendritic spine loss is commonly seen in hippocampal pyramidal neurons and dentate granule cells in patients with temporal lobe epilepsy and may occur in isolation or associated with varicose swelling of the dendritic branches [52][53][54][55][56]. Similar findings of spine loss and dendritic swelling have also been documented in pyramidal neurons of neocortex, including sites distant from the primary epileptogenic focus [57].…”
Section: Dendritic Abnormalities In Epilepsymentioning
confidence: 99%
“…A standardised neuropathological evaluation of the hippocampus revealed Ammon's horn sclerosis (AHS), i.e. segmental neuronal cell loss in CA1 as well as CA3/4, gliosis, and axonal reorganisation [12]. The temporal lobe specimen showed heterotopic neurons in the white matter.…”
Section: Human Brain Tissuementioning
confidence: 99%
“…From then on, there were several studies that reported on the presence of senile plaques in patients with epilepsy [129]. Along with amyloid deposition, the other neuropathologic signature of dementia, tau, has also been reported in human epilepsy patients and in animal models of epilepsy [130]. Besides, atrophy of the mesial and lateral temporal regions on MRI and hypometabolism in the basal temporal region demonstrated by positron emission tomography studies were characteristic finding in both conditions [131,132].…”
Section: Myoclonus and Seizuresmentioning
confidence: 93%